IMPACT OF AN ACTIVE AGING PROGRAM IN THE COMMUNITY CONTEXT - CASE STUDY - Ana Da Conceição Alves Faria; Maria Manuela Ferreira Pereira Da Silva Martins; Olga Maria Pimenta Lopes Ribeiro; Bárbara Pereira Gomes (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Introduction: Active aging programs are fundamental in improving the health condition and healthy lifestyles of the elderly. Objective: To analyze the impact of an active aging program on the functional capacity and lifestyles of the elderly. Method: Case study with evaluation before and after an active aging program, implemented for 16 weeks, in a sample of 8 elderly people. Results: After the program, the elderly had fewer episodes of: musculoskeletal pain, loss of urine, feelings of sadness and changes in memory. They improved their adherence to physical activity, healthy eating habits, preventive and relational behaviors, as well as stress management. The handgrip strength increased and the static and dynamic balance improved significantly. Conclusion: This active aging program demonstrated gains with the intervention of rehabilitation nurses in the functional capacity and adherence of the elderly to healthy lifestyles.